Effect of Agrochemical Exposure on Schistosoma mansoni Cercariae Survival and Activity. (4th June 2020) - Jones, Devin K.; Davila, David D.; Nguyen, Karena H.; Rohr, Jason R.
Abstract: Singular use of activity assays or staining dyes to assess pathogen agrochemical tolerance can underestimate tolerance if pesticides cause sublethal effects. We exposed Schistosoma mansoni cercariae, the aquatic life stage of this trematode that infects humans, to 4 insecticides at 5 concentrations using a 24‐h time‐to‐death assay. We used Trypan blue dye, which stains dead tissue, and activity assays simultaneously to discriminate dead from live but paralyzed individuals. Whereas cypermethrin, deltamethrin, and dimethoate exposure did not affect cercariae at any ecologically relevant concentrations, methamidophos exposure increased survival of cercariae compared with those in the controls. This was because methamidophos‐induced paralysis reduced cercarial activity and thus energy expenditures, extending the lifespan of this short‐lived parasite that causes human schistosomiasis. These findings highlight that sublethal effects should be considered when pesticide effects on disease are under investigation. Environ Toxicol Chem 2020;39:1421–1428. © 2020 SETAC Abstract : Historically, investigation of agrochemical effects on pathogens has long used activity assays or staining dyes; singular use of either method can misestimate pesticide tolerance if sublethal effects occur as a result of pesticide exposure. We found an organophosphate insecticide to induce paralysis of Schistosoma mansoni cercariae, increasing survival over a 24‐h period, and that cercariae were extremely tolerant to nominal pesticide concentrations that exceeded estimated environmental concentrations. We suggest future investigations examining pesticide effects on disease use dye and activity assays in tandem.